Romanticizing Brahms: early recordings and the reconstruction of Brahmsian identity - Scott, Anna (Leiden Anna Scott, 2014)
Despite most pianists' claims of historical deference and creative agency, their performances of Brahms's piano works are nothing like the early-recorded performances of the composer and his students: gaps that are mediated by understandings of Brahms's Classical canonic identity, the performance norms that protect that identity, and those norms' underlying aesthetic ideology of control. This predication of Brahmsian identity on restraint leaves the composer and his students in a precarious situation, as their recordings evidence an approach that is governed by the inhibitions typically associated with Romanticism. This volume seeks to problematize understandings of Brahms's identity: by investigating the origins and vestiges of the aesthetic ideology of control; by analysing and copying the recordings of pianists in the composer's inner circle; and by applying these pianists' styles in ways that are just as disruptive to modern notions of Brahmsian identity as their early-recorded models. In so doing, a thoroughly Romantic performance style emerges that catalyses a fundamental shift in understanding as related to Brahms's identity; thereby opening up a new palette of expressive and technical resources, and both elucidating and narrowing persistent gaps between modern and early-recorded Brahms style, as well as between what performers believe, know, and ultimately do.
Proefschrift ter verkrijging van de graad van Doctor aan de Universiteit Leiden op gezag van de Rector Magnificus prof. mr. C.J.J.M. Stolker, volgens besluit van het College voor promoties te verdedigen op 11 december 2014.